The Effects of Emotional Intelligence, Job Crafting, and Perceived Organizational Support on Work Engagement Through Job Satisfaction at A Coffee Shop in Jakarta - Verdana Akbar; Dewi Susita; Widya Parimita (Indonesian Journal of Multidisciplinary Science, 2026)
Employee work engagement is an important factor in achieving organizational effectiveness, particularly in the food and beverage industry, where employees face dynamic workloads and intensive customer interactions. However, factors influencing work engagement, including emotional intelligence, job crafting, perceived organizational support, and job satisfaction, remain challenging aspects within service-based organizations. This study aims to examine the effects of emotional intelligence, job crafting, and perceived organizational support on work engagement through job satisfaction as a mediating variable among employees of Kaizen Heritage coffee shops in Jakarta. This research employed a quantitative approach with a causal research design. Data were collected through questionnaires distributed to 158 employees selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that job crafting and job satisfaction had positive and significant effects on work engagement, whereas emotional intelligence and perceived organizational support did not have significant direct effects. Furthermore, job crafting and perceived organizational support significantly improved job satisfaction, while emotional intelligence did not demonstrate a significant influence. The mediation analysis revealed that job satisfaction significantly mediated the relationships between job crafting, perceived organizational support, and work engagement but did not mediate the relationship between emotional intelligence and work engagement. This study concludes that employee engagement in the food and beverage industry is strongly influenced by proactive work adaptation and positive job experiences. Therefore, organizations should enhance job crafting opportunities and improve employee satisfaction through supportive management practices to strengthen work engagement.